Students’ mathematics achievement in Mindanao context: A meta-analysis - Callaman, Roar Abalos; Itaas, Estela Corro (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2020)
Over the years, there have been several studies exploring the factors affecting mathematics achievement. However, no study, specifically in the Mindanao context has attempted to summarize or illustrate the model for these sets of studies. This study aims to analyze the overall effect size of the factors on the student’s achievement in mathematics. The causal-comparative research design was utilized to synthesize the existing research about the student-related, teacher-related, and school-related factors that have -greatly influenced students’ mathematics achievement. Through the use of a multi-stage sampling design, 200 existing studies were funneled down to 50 with 158 effect sizes which met the inclusion criteria coming from the different colleges and universities in Mindanao. To determine the significant factors be included in the model that significantly influence students’ achievement, Hierarchical Linear Modeling (HLM) was utilized. The findings revealed that the overall effect sizes have a small effect on mathematics achievement. On the other hand, mathematical skills, attitude, and self-efficacy are found to be the predictors of students’ mathematical achievement. Further, it was concluded that the type of school where the student is studying could cause significant variation in the effect sizes. It is recommended that educational institutions may review regularly the curriculum addressing the disparity of achievement between public and private schools. Also, teachers may utilize varied teaching strategies so that students would develop interest and positive learning attitudes towards mathematics.